ASSESSMENT AND ANALYSIS OF THE LEVEL OFPHYSICAL DEVELOPMENT OF HIGH SCHOOLSTUDENTS BASED ON NORMATIVE STANDARDS - Erkaboyev Oybek Muxammadjonovich (Proximus Journal Publishing, 2025)
The article presents the results of experimental studies of physical fitness of graduates of secondary schools in the city of Fergana and their comparative analysis with the regulatory requirements of the State standards for physical education, the requirements for physical fitness of young people and Alpomish health tests.
Keywords: technique; monitoring; Standard